2019
DOI: 10.18295/squmj.2018.18.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Adenotonsillectomy on the Cognitive and Behavioural Function of Children Who Snore: A naturalistic observational study

Abstract: Objectives: This study aimed to evaluate cognitive and behavioural changes among 9–14-year-old Omani children with obstructive sleep apnoea (OSA) after an adenotonsillectomy (AT). Methods: This naturalistic observational study was conducted at the Sultan Qaboos University Hospital, Muscat, Oman, between January 2012 and December 2014. Omani children with adenotonsillar hypertrophy (ATH) underwent overnight polysomnography and those with confirmed OSA were scheduled for an AT. Cognitive and behavioural evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
8
1
Order By: Relevance
“…A study done by Al-Zaabi et al (2018) aimed to evaluate cognitive and behavioral changes among children aged nine to 14 with OSA after adenotonsillectomy. The results of the study showed a 33% improvement in neurocognitive function and general intellectual ability, as well as a 21% reduction in inattention and hyperactivity scores, thus showing evidence of the effectiveness of adenotonsillectomy in improving ADHD-like symptoms among children [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study done by Al-Zaabi et al (2018) aimed to evaluate cognitive and behavioral changes among children aged nine to 14 with OSA after adenotonsillectomy. The results of the study showed a 33% improvement in neurocognitive function and general intellectual ability, as well as a 21% reduction in inattention and hyperactivity scores, thus showing evidence of the effectiveness of adenotonsillectomy in improving ADHD-like symptoms among children [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…At least eleven papers (2776 patients) were considered eligible for our analysis [3,[56][57][58][59][60][61][62][63][64][65], of which four were prospective cohort studies [58,61,62,64] and seven were randomized controlled trials [3,56,57,59,60,63,65] (see Table 1). The main features of the data of the included articles and the studies measured with time of follow-up are summarized in Table 2.…”
Section: Retrieving Researchmentioning
confidence: 99%
“…Most of patients performed polysomnography, reporting Apnea/Hypopnea Index (AHI) [3,[56][57][58][59][60][61][63][64][65], Oxygen Desaturation Index (ODI) [52,54,56,60] or Obstructive Apnea Index (OAI) [61]. Some studies further measured percentage sleep time with end-tidal CO2 values > 50 mmHG [55,56], OSA-18 items [56,60,64] or the Korean version of it (KOSA-18) [63].…”
Section: Retrieving Researchmentioning
confidence: 99%
See 2 more Smart Citations